2020
DOI: 10.32734/sumej.v3i1.3310
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ACE Gene Polymorphism and Hypertension in Stroke Ischemic Patients

Abstract: Stroke is the third highest cerebrovascular disease in the world with high mortality and disability rate that is mostly dominated by ischemic stroke. Genetic factor that had been reported to have an indirect effect in increasing the incidence of ischemic stroke is ACE gene polymorphism. ACE gene polymorphism is characterized by the insertion marked by letter (I) or deletion marked by letter (D) on intron 16, chromosome 17. ACE gene polymorphism has drawn a lot of attention from scientists and had been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Based on the allele and its genotype, there is no significant correlation between the ACE gene polymorphism and HTN in patients with IS. In this study, the I allele (72.1%) of the ACE gene polymorphism was more dominant than the D allele (27.9%) in patients with hypertensive IS ( 37 ). In addition, research conducted in South India ( 38 ) showed a link between the ACE II genotype and the I allele, which was exacerbated by factors such as smoking and diabetes among patients with IS.…”
Section: Discussionmentioning
confidence: 54%
“…Based on the allele and its genotype, there is no significant correlation between the ACE gene polymorphism and HTN in patients with IS. In this study, the I allele (72.1%) of the ACE gene polymorphism was more dominant than the D allele (27.9%) in patients with hypertensive IS ( 37 ). In addition, research conducted in South India ( 38 ) showed a link between the ACE II genotype and the I allele, which was exacerbated by factors such as smoking and diabetes among patients with IS.…”
Section: Discussionmentioning
confidence: 54%